Identification of Clinical Relevant Molecular Subtypes of Pheochromocytoma - Saddozai, Umair Ali Khan; Wang, Fengling; Akbar, Muhammad Usman; Zhang, Lu; An, Yang; Zhu, Wan; Xie, Longxiang; Li, Yongqiang; Ji, Xinying; Guo, Xiangqian (Frontiers in Endocrinology, 2021)
Pheochromocytoma (PCC) is a rare neuroendocrine tumor of adrenal gland with high rate of mortality if being diagnosed at a late stage. Common symptoms of pheochromocytoma include headache, anxiety, palpitation and diaphoresis. Different treatments are under observation for PCC but still there is no effective treatment option to be determined. Recently, the gene expression profiling of various tumors provides new subtype-specific options for targeted therapies. In this study, using data sets from TCGA and the GSE19422 cohorts, we identified two distinct PCC subtypes with distinct gene expression patterns. Genes enriched in Subtype I PCCs were involved in dopaminergic synapse, nicotine addiction, long-term depression pathways, while genes enriched in subtype II PCCs were involved in protein digestion and absorption, vascular smooth muscle contraction, ECM receptor interaction pathways. We further identified subtype specific genes such as ALK, IGF1R, RET, RSPO2 for subtype I while EGFR, ESR1 and SMO for subtype II, the overexpression of which lead to cell invasion and tumorigenesis. These genes identified in present research may serve as potential subtype-specific therapeutic targets to understand the underlying mechanisms of tumorigenesis. Our findings may further guide towards the development of targeted therapies and potential molecular biomarkers against PCC.